Processi motivazionali, volitivi e autopresentazione efficace in adolescenza: risultati di uno studio longitudinale - Fiorenzo Laghi; Laura Picone; Antonia Lonigro; Martina Fossati (LED Edizioni Universitarie, 2012)
Motivational and Volitional Processes and Effective Self-presentation in Adolescence: The Results of a Longitudinal Study The latest research in the learning field shows the strictly interconnected motivational and volitional processes as the strongest predictors of school achievement. This achievement is not solely determined by aptitudes, but other factors like motivational and volitional factors, relations with peers and with teachers, and feelings of self-esteem and self-efficacy come into play and significantly affect the learner's performance and classroom adjustment. The 3-year longitudinal study presented here aimed to analyze which motivational, volitional and self-presentation components foster school learning in a sample of 95 Italian high school students. The IST-2000 and a specific battery for assessing motivation and volition were administered in the classroom on two occasions with a three-year interval. Results revealed that students, who increased their aptitudes in the last year, had higher levels of intrinsic motivation and volition, and were more able to understand others' intentions and emotions than students who reported a worsening of their aptitudes. In the light of these and other findings presented in the paper, it discusses the importance of motivation and self-presentation in the school context.